ANALISIS KEJENUHAN BELAJAR PESERTA DIDIK DI MASA PANDEMI COVID-19 PADA KELAS XI IIS SMA NEGERI 9 PONTIANAK - Kardianti, Agus; Asrori, M; Purwanti, Purwanti (Universitas Tanjungpura, 2022)
This study aims to determine the learning saturation of students during the Covid-19 pandemic in class XI IIS SMA Negeri 9 Pontianak. The research method used is descriptive in the form of survey study research. The data sources of this research are the students of class XI IIS wit a total of 45 students. Techniques and data collection tools used in this research is indirect communication with a questionnaire. The results showed that the analysis of student learning saturation during the Covid-19 pandemic in class XI IIS SMA Negeri 9 Pontianak as a whole reached 67.4% with a high category which means that the student experienced learning saturation. Emotional exhaustion 67.4% in the high category, 67% physical fatique in the high category, cognitive fatigue 66,3% in the moderate category, 70% loss in the high category. Efforts made by quidance and counseling teachers to overcome learning saturation during the Covid-19 pandemic by providing information services 69.3% in the high category, tutoring services 72.4% in the high category, individual counseling services 49.3% in the high category, group counseling service 66% with moderate categories, and group counseling services 67.5% with high categories.